Investigating Dishonesty-Does Context Matter? - Waeber, Aline (Frontiers in Psychology, 2021)
This paper introduces frame-specific randomization devices to vary the situational context of an online lying experiment. Participants are asked to report outcomes of random draws from two different sources of uncertainty—decimals of the value of a stock index or a neutrally framed random number generator. The findings show that the frame-specific randomization device is not prone to the social norm effects documented in the literature. Because different environments can evoke different norms, I replicate the experiment in the more constrained setting of a traditional physical laboratory revealing no systematic differences in behavior. Furthermore, I am not able to show that participants who take longer to report are more honest and this is specific to the physical laboratory environment. Finally, the findings reveal gender differences in honesty depending on the environment—males are more honest when they participate in the laboratory as opposed to online.